TINGKAT KOMPLEMEN ARSITEKTURAL ELEMEN NATURAL DAN BUATAN DALAM PENGUNGKAPAN FUNGSIONALITAS RUANG KOTA - Firasyan, Raisa; Pangarso, F.X. Budiwidodo (Jurnal Riset Arsitektur, 2023)
Abstract - Architecture is always pervaded by the context in which it is placed. This is of course closely relatedto the visual impression created on a large scale, namely the city scale. A city can have an identity because thearchitecture in it is related to its nature. The elements that make up the urban space will adapt and anticipateusing designs that respond to geographic facts. These adjustments can lead to dif erent visual goodness values.Cities are often simply separated from nature, coupled with the destruction of nature caused byindif erent humans. This thinking is called binary pairs, where a city and nature are considered contradictoryand cannot be united. Humans raise their hands against exploitation and environmental pollution. Valssonwrites that this thinking is wrong, and can be corrected by the method of complementarity. Therefore, the focusof this research is to find the level of complementarity between the geographical facts of the city and thearrangement of architectural elements through panoramic view of the city's space and functional condition ofthe Segiri Market Area, Samarinda.This research was conducted qualitative descriptive with the help of pictorial analytic technique. Theresearch aims to contribute a study of urban aesthetics, with a focus on the complementarity of urban elements.This research is theory-based from several literatures and online observation of the object of study. The datacollected is associated with a theoretical study of urban literature of urban aesthetics.Samarinda City is a waterfront city which is crossed by the Mahakam River and its tributary, theKarang Mumus River. Even though it is a tributary, the Karang Mumus River has a fairly large width of 40meters. This geographical fact relates to the surrounding architectural elements visually. These relationshipscan be complementary or analogous, dif ering in each area of observation. The review of the complementarity ofeach observation area is accompanied by observations of the activities in it, and dif erences in human activitypatterns are found based on these relationships.It is hoped that this research can provide benefits in the form of a study of urban aesthetics, with afocus on the relationship between natural and artificial elements of urban space and activity patterns in urbanspace in the Segiri Market Area, Samarinda. In addition, it is hoped that this research can become additionalknowledge and as a reference and basis for further research.Keywords: complementarity, urban elements, functional townscape, Samarinda